PEMBAHARUAN HUKUM ISLAM DI MESIR DAN SUDAN: STUDI KOMPARASI - Asrizal Saiin; Hasbi Umar; Hermanto Harun (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This paper discusses how the renewal of Islamic law occurred in Egypt and Sudan. This study uses a qualitative research method with a normative approach. The data source used in this study is a secondary data source, because it only examines the literature or literature. From the results of this study, it can be understood that the role of the countries of Egypt and Sudan in fighting for qanunization (taqnin) and the formalization of Islamic law is very large. Even though they have to go through the challenges of Western imperialism and secularism, so that Islamic societies and countries have variations in responding to Western civilization today. The renewal of Islamic law in Egypt and Sudan occurred because of the struggle of Muslims in Egypt and Sudan with the rulers of the Islamic world, between secularism and Islamic law.